Improving competitive strategic decisions of Chinese coal companies toward green transformation: A hybrid multi-criteria decision-making model. (March 2022) - Wang, Junqi; Cao, Hongjun
Abstract: The growth of renewable energy has accelerated the decline of the coal industry. Therefore, coal enterprises urgently need to make the strategic decision toward green transformation to enhance their competitiveness. This research proposes an improved multi-criteria decision-making (MCDM) framework to help coal enterprises in their strategic decision-making. First, based on an analysis of macro environment, industry environment, and enterprise internal environment, a mixed network structure model is constructed; then, the priority of three competitive strategy schemes is analyzed. Based on this priority, sensitivity analysis is used to verify the impact of indicators and external environment on the final decision-making results. The results show that: (1) Differentiation strategy is optimal for coal enterprises over the green transition period. (2) There are seven key indicators that affect the stability of strategic decision-making. These are the development trend of green economy, the concept of green culture, the threat of potential entrants, the bargaining power of suppliers, the bargaining power of buyers, the enhanced allocation of green resources, and the rise of transformation costs. (3) The threat of potential entrants, the enhancement of green resource allocation ability, and the increase of transformation cost greatly influence the final decision. (4) The bargaining power of suppliers and buyers only affects the order of differentiation and centralization strategy. (5) The development trend of green economy and the concept of green culture exert little influence on the ranking of differentiation and centralization strategy, and the changing trend is relatively stable. Finally, based on the results, competitive strategic suggestions for coal enterprises from three aspects and policy suggestions are put forward to ensure the green transformation of coal enterprises from the macro level. Highlights: A hybrid MCDM is proposed, integrating PEST, Porter five forces, BOCR, and ANP. Differentiation strategy is identified as the best choice for coal enterprises. Despite external interference, the decision-making result remains stable. Seven key indicators are identified by index sensitivity analysis.